2019
DOI: 10.1016/j.micpath.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro phagocytosis and intracellular killing of Pasteurella multocida B:2 by phagocytic cells of buffaloes

Abstract: Pasteurella multocida B:2 is a Gram-negative organism causing haemorrhagic septicaemia (HS) in buffaloes. It causes severe pulmonary infection, leading to infiltration of numerous macrophages and neutrophils. Despite the inflammatory response, buffaloes succumb to HS. This study aims to evaluate the in-vitro efficacy of macrophages and neutrophils of buffalo following exposure to P. multocida B:2. In-vitro infections were done using 10 ⁷ cfu/ml of P. multocida B:2 for Group 1, Escherichia coli for Group 2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Moreover, recent in-vitro study revealed that P. multocida B:2 has high ability to cause death of phagocytic cells, particularly in the neutrophil and macrophage following infection with P. multocida B:2. This might be attributed by the release of large amount of LPS endotoxin upon intracellular lysis of P. multocida B:2 [20]. Crucially, during acute phase of infection, LPS-induced immune cell death could also results in collateral tissue damage, aggravating sepsis-like response [18,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, recent in-vitro study revealed that P. multocida B:2 has high ability to cause death of phagocytic cells, particularly in the neutrophil and macrophage following infection with P. multocida B:2. This might be attributed by the release of large amount of LPS endotoxin upon intracellular lysis of P. multocida B:2 [20]. Crucially, during acute phase of infection, LPS-induced immune cell death could also results in collateral tissue damage, aggravating sepsis-like response [18,21].…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type P. multocida B:2 isolated from an outbreak of HS was used in this study. It was prepared to achieve an infective dose of 1.0 × 10 7 cfu/ml of live P. multocida B:2 as previously described [20]. Briefly, it was cultured onto blood agar and incubated at 37°C for 24 h. Four colonies from this blood agar were transferred into a brain-heart infusion broth and incubated at 37°C for 18 h with shaking at 150 rpm for.…”
Section: Preparation Of P Multocida B:2 Inoculum and Purification Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical models to evaluate outbreak data and potential intervention strategies have been described [347]. In vitro assays have been performed using macrophages and aortic endothelial cells [348][349][350][351]. Mouse models can play an important role in investigation of pathogenesis and vaccine development [317,[351][352][353][354][355][356][357][358][359][360][361][362][363].…”
Section: Hemorrhagic Septicemiamentioning
confidence: 99%
“…Mouse models can play an important role in investigation of pathogenesis and vaccine development [317,[351][352][353][354][355][356][357][358][359][360][361][362][363]. Rats with or without immunosuppression have also been used to explore pathogenesis and novel vaccines [349][350][351][364][365][366]. Rabbits are occasionally used for vaccine evaluation and, along with mice, were recently used to evaluate a novel phage lysate marker vaccine along with a DIVA ELISA [358].…”
Section: Hemorrhagic Septicemiamentioning
confidence: 99%